Transitional hypoxia during peatland water table fluctuations drives high N2O fluxes via shifting microbial pathways - Mohit Masta; Fahad Ali Kazmi; Mikk Espenberg; Triinu Visnapuu; Louise B. Sennett; Lauri Eving; Dominika Lewicka-Szczebak; Sushmita Deb; Ramita Khanongnuch; Laura Kuusemets; Priit Kupper; Klaus Butterbach-Bahl; et al. (Environmental Research, 2026)

Do climatic conditions alter fine root exudation or metabolic profiles in Norway spruce? - Aliya Sultonova; Linda Rusalepp; Priit Kupper; Mikk Espenberg; Marili Sell; Kärt Kanger; Gristin Rohula-Okunev; Marian Klaus; Ivika Ostonen (Rhizosphere, 2026)

Needle and bark specialised metabolites of Norway spruce depend on forest site type and stand composition - Bikash Kharel; Arvo Tullus; Linda Rusalepp; Taavi Reinthal; Gristin Rohula-Okunev; Priit Kupper (Plant Ecology, 2026)

Above- and belowground acclimation of morphological traits of silver Birch to competition conditions and elevated moisture regimes of air and soil - Katrin Rosenvald; Marco M. Lehmann; Ivika Ostonen; Gristin Rohula-Okunev; Priit Kupper; Arvo Tullus (European Journal of Forest Research, 2026)

Dry and wet periods determine stem and soil greenhouse gas fluxes in a northern drained peatland forest - Reti Ranniku; Ülo Mander; Jordi Escuer-Gatius; Thomas Schindler; Priit Kupper; Arne Sellin; Kaido Soosaar (Science of The Total Environment, 2024)

Night-time water relations and gas exchange in cut shoots of five boreal dwarf shrub species: impact of soil water availability - Priit Kupper; Arvo Tullus; Gristin Rohula-Okunev (Physiology and Molecular Biology of Plants, 2023)

Effects of air humidity and soil moisture on secondary metabolites in the leaves and roots of Betula pendula of different competitive status - Bikash Kharel; Linda Rusalepp; Biplabi Bhattarai; Ants Kaasik; Priit Kupper; Reimo Lutter; Pille Mänd; Gristin Rohula-Okunev; Katrin Rosenvald; Arvo Tullus (Oecologia, 2023)

Assessing the fine root growth dynamics of Norway spruce manipulated by air humidity and soil nitrogen with deep learning segmentation of smartphone images - Marili Sell; Abraham George Smith; Iuliia Burdun; Gristin Rohula-Okunev; Priit Kupper; Ivika Ostonen (Plant and Soil, 2022)

Predawn disequilibrium between soil and plant water potentials in light of climate trends predicted for northern Europe - Ott Kangur; Priit Kupper; Arne Sellin (Regional Environmental Change, 2017)

Impact of high daytime air humidity on nutrient uptake and night-time water flux in silver birch, a boreal forest tree species - Priit Kupper; Gristin Rohula; Liina Inno; Ivika Ostonen; Arne Sellin; Anu Sõber (Regional Environmental Change, 2017)

Growth of northern deciduous trees under increasing atmospheric humidity: possible mechanisms behind the growth retardation - Arne Sellin; Meeli Alber; Markku Keinänen; Priit Kupper; Jenna Lihavainen; Krista Lõhmus; Elina Oksanen; Anu Sõber; Jaak Sõber; Arvo Tullus (Regional Environmental Change, 2017)

Endogenous regulation of night-time water relations in hybrid aspen grown at ambient and elevated air humidity - Gristin Rohula; Ingmar Tulva; Arvo Tullus; Anu Sõber; Priit Kupper (Regional Environmental Change, 2017)

The competitive status of trees determines their responsiveness to increasing atmospheric humidity – a climate trend predicted for northern latitudes - Arvo Tullus; Priit Kupper; Ants Kaasik; Hardi Tullus; Krista Lõhmus; Anu Sõber; Arne Sellin (Global Change Biology, 2017)
The interactive effects of climate variables and tree–tree competition are still insufficiently understood drivers of forest response to global climate change. Precipitation and air humidity are predicted to rise concurrently at high latitudes of the Northern Hemisphere. We investigated whether the growth response of deciduous trees to elevated air humidity varies with their competitive status. The study was conducted in seed‐originated silver birch and monoclonal hybrid aspen stands grown at the free air humidity manipulation ( FAHM ) experimental site in Estonia, in which manipulated stands ( n = 3 for both species) are exposed to artificially elevated relative air humidity (6–7% over the ambient level). The study period included three growing seasons during which the stands had reached the competitive stage (trees were 7 years old in the final year). A significant ‘treatment×competitive status’ interactive effect on growth was detected in all years in birch ( P 0.01) and in one year in aspen stands ( P = 0.015). Competitively advantaged trees were always more strongly affected by elevated humidity. Initially the growth of advantaged and neutral trees of both species remained significantly suppressed in humidified stands. In the following years, dominance and elevated humidity had a synergistic positive effect on the growth of birches. Aspens with different competitive status recovered more uniformly, attaining similar relative growth rates in manipulated and control stands, but preserved a significantly lower total growth yield due to severe initial growth stress. Disadvantaged trees of both species were never significantly affected by elevated humidity. Our results suggest that air humidity affects trees indirectly depending on their social status. Therefore, the response of northern temperate and boreal forests to a more humid climate in future will likely be modified by competitive relationships among trees, which may potentially affect species composition and cause a need to change forestry practices.

Effects of enhanced hydraulic supply for foliage on stomatal responses in little-leaf linden (Tilia cordata Mill.) - Arne Sellin; Priit Kupper (European Journal of Forest Research, 2007)

Spatial variation in sapwood area to leaf area ratio and specific leaf area within a crown of silver birch - Arne Sellin; Priit Kupper (Trees, 2006)

Effects of branch position on water relations and gas exchange of European larch trees in an alpine community - Priit Kupper; Arne Sellin; John Tenhunen; Markus Schmidt; Märt Rahi (Trees, 2006)

Effects of light availability versus hydraulic constraints on stomatal responses within a crown of silver birch - Arne Sellin; Priit Kupper (Oecologia, 2005)